Coronavirus Disease 2019-Related Multisystem Inflammatory Syndrome in Children: A Systematic Review and Meta-Analysis - Ji-Gan Wang; Zhi-Juan Zhong; Meng Li; Jun Fu; Yu-Heng Su; You-Min Ping; Zi-Ji Xu; Hao Li; Yan-Hao Chen; Yu-Li Huang (Biochemistry Research International)
Background. This study aimed to describe the clinical symptoms, laboratory findings, treatment, and outcomes of coronavirus disease 2019-related multisystem inflammatory syndrome in children to provide a reference for clinical practice. Methods. We employed a literature search of databases such as PubMed, Web of Science, EMBASE, and Johns Hopkins University for articles on COVID-19-related multisystem inflammatory syndrome in children published between April 1, 2020, and January 15, 2021. High-quality articles were selected for analysis on the basis of their quality standard scores. Using R3.6.3 software, meta-analyses of random- or fixed-effects models were used to determine the prevalence of comorbidities. Subgroup analysis was also performed to determine heterogeneity. Results. A total of 57 articles (2,290 pediatric patients) were included in the study. Clinical Manifestations. :ncidences of fever, gastrointestinal symptoms, respiratory symptoms, and musculoskeletal symptoms (myalgias or arthralgias) were 99.91% (95% CI: 99.67–100%), 82.72% (95% CI: 78.19–86.81%), 53.02% (45.28–60.68%), and 14.16% (95% CI: 8.4–21.12%), respectively. The incidences of rash, conjunctival injection, lymphadenopathy, dry cracked lips, neurologic symptoms (headache, altered mental status, or confusion), swollen hands and feet, typical Kawasaki disease, and atypical Kawasaki disease were 59.34% (95% CI: 54.73–63.87%), 55.23% (95% CI: 50.22–60.19%), 27.07% (95% CI: 19.87–34.93%), 46.37% (95% CI: 39.97–52.83%), 28.87% (95% CI: 22.76–35.40%), 28.75% (95% CI: 21.46–36.64%), 17.32% (95% CI: 15.44–19.29%), and 36.19% (95% CI: 21.90–51.86%), respectively. The incidences of coronary artery dilation, aneurysm, pericardial effusion, myocarditis, myocardial dysfunction, high troponin, and N-terminal pro-B-type natriuretic peptide were 17.83%, 6.85%, 20.97%, 35.97%, 56.32%, 76.34%, and 86.65%, respectively. The incidences of reduced lymphocytes, thrombocytopenia, hypoalbuminemia, elevated C-reactive protein, ferritin, LDH, interleukin-6, PCT, and FIB were 61.51%, 26.42%, 77.92%, 98.5%, 86.79%, 80.59%, 89.30%, 85.10%, and 87.01%, respectively. PICU Hospitalization Rate and Mortality. The incidences of PICU hospitalization or with shock were 72.79% and 55.68%, respectively. The mortality rate was 1.00%. Conclusion and Relevance. PICU hospitalization and shock rates of multisystem inflammatory syndrome in children associated with COVID-19 were high, and its cumulative multiorgans and inflammatory indicators are increased, but if treated in time, the mortality rate was low.